2001
DOI: 10.1046/j.1440-1614.2001.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Critical Incidents and Their Effect on Outcome in an Adolescent Inpatient Service

Abstract: Critical incidents are common among hospitalized adolescents and result in a poorer outcome. Increased structure during the evenings, problem-solving and social skills programmes for patients, and specific training for staff regarding management and minimization of critical incidents should be provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 10 publications
2
28
5
Order By: Relevance
“…In our study, most violent incidents were caused by boys, but girls also instigated a significant percentage of these events. This finding is in concordance with that of other investigators (Barton et al 2001;Dean et al 2008), mostly in adults (Drori et al 2017;Iozzino et al 2015). However, Ryan et al (2004) observed that similar to boys, girls were as likely to assault a staff member at least once, although boys tended to display higher levels of external aggression and engage in repeated assaults.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, most violent incidents were caused by boys, but girls also instigated a significant percentage of these events. This finding is in concordance with that of other investigators (Barton et al 2001;Dean et al 2008), mostly in adults (Drori et al 2017;Iozzino et al 2015). However, Ryan et al (2004) observed that similar to boys, girls were as likely to assault a staff member at least once, although boys tended to display higher levels of external aggression and engage in repeated assaults.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in concordance with that of other investigators (Barton et al . ; Dean et al . ), mostly in adults (Drori et al .…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of therapist's absence in all patients with incidents can be explained by findings of previous studies that identified unstructured times of day as a risk factor for incidents (7,8): due to work schedules therapist's absence often occurs in the afternoon or evening. Our results suggest that therapist's absence may be a common risk factor for incidents, but not a factor that differentiates patients with repeat from patients with single incidents.…”
Section: Discussionmentioning
confidence: 98%
“…In the Anglo-American literature, prevalence ranges between 17% and 61% for non-suicidal self-injury (3)(4)(5) and 20%-90% for overt aggressive behavior (5), making prediction of such incidents a core concern of clinical research. The literature on aggressive or self-harming incidents in clinical settings indicates that a few patients are often responsible for a disproportionate number of incidents (6,7) and that previous episodes of aggressive or selfharming incidents are risk factors for subsequent incidents (8)(9)(10). Findings of an early-life exposure to stress (e.g., a history of abuse or parental neglect) (3,11) and an exposure to psychosocial risk factors (1, 3) support the model of an altered stress reactivity (12) in patients with aggressive or self-harming incidents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation